2009
DOI: 10.1007/s11240-009-9653-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant growth regulators and l-glutamic acid on shoot organogenesis in the halophyte Leymus chinensis (Trin.)

Abstract: The halophyte Leymus chinensis (Trin.) is a perennial rhizome grass (tribe Gramineae) that is widely distributed in China, Mongolia and Siberia, where it is produced as a forage product. In this report, we establish a highly reproducible plant regeneration system through somatic embryogenesis. Two explants, mature seeds and leaf base segments were used; these parts displayed different responses to combinations of growth factors that affect embryogenic callus induction, callus type optimization and plant regene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 50 publications
4
44
0
1
Order By: Relevance
“…However, the mechanism of totipotency is still less understood. Many factors affect shoot regeneration in plant tissue culture: such as genotype Glowacha et al 2010;Park et al 2011), exogenous and endogenous hormones (Jiménez 2005;Barreto et al 2010;Sun and Hong 2010;Huang et al 2012), carbon sources (Huang and Liu 1998;Iraqi et al 2005;Huang et al 2006;Silva 2010;Feng et al 2010), and osmotic requirements (Geng et al 2008;Pan et al 2010;Huang et al 2012). Despite many shoot regeneration and transformation protocols developed in rice culture, the regeneration frequency is low and varies highly among cultivars (Al-Khayri et al 1996;Hoque and Mansfied 2004;Khaleda and Al-Forkan 2006;Zhao et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanism of totipotency is still less understood. Many factors affect shoot regeneration in plant tissue culture: such as genotype Glowacha et al 2010;Park et al 2011), exogenous and endogenous hormones (Jiménez 2005;Barreto et al 2010;Sun and Hong 2010;Huang et al 2012), carbon sources (Huang and Liu 1998;Iraqi et al 2005;Huang et al 2006;Silva 2010;Feng et al 2010), and osmotic requirements (Geng et al 2008;Pan et al 2010;Huang et al 2012). Despite many shoot regeneration and transformation protocols developed in rice culture, the regeneration frequency is low and varies highly among cultivars (Al-Khayri et al 1996;Hoque and Mansfied 2004;Khaleda and Al-Forkan 2006;Zhao et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Plant tissue culture of LC has been investigated using nearly all readily available explants such as mature embryos (Liu et al, 2002b;Kim et al, 2005), mature seeds (Cui et al, 1990;Qu et al, 2004;Kim et al, 2005;Wei et al, 2005;Kong et al, 2008;, 2010a, leaf base segments (Liu et al, 2002b;Kim et al, 2005;, 2010a, rhizoma (Gao, 1982;Lu et al, 2009), immature inflorescence , immature spikes (Liu et al, 2002b;Zhang et al, 2007), and root segments ), shown in Table 1. In our previous studies 2010a), mature seed is considered as the optimal explants to induce embryogenic callus, with 56.4 ~ 88.3% of callus induction frequencies.…”
Section: Explants Typementioning
confidence: 99%
“…In our previous studies 2010a), mature seed is considered as the optimal explants to induce embryogenic callus, with 56.4 ~ 88.3% of callus induction frequencies. Similar results have been observed in reports of Cui et al (1990) and Kim et al (2005) that found mature seeds could produced the highest callus induction frequencies among young rhizome, embryos and leaves as explants, respectively.…”
Section: Explants Typementioning
confidence: 99%
See 1 more Smart Citation
“…), a perennial rhizome grass in the Gramineae family, has halophytic ancestors and could be a potential source of halotolerance genes for glycophytic crop plants. [10] This species is widely distributed throughout Northern China, Mongolia and Siberia, [21,22] having intrinsic potential to thrive under environmentally high alkaline-sodic soil conditions (pH 8.5 to 11.5). Due to its good characteristics, L. chinensis has been commonly used to protect the soil from desertification in northern China.…”
Section: Introductionmentioning
confidence: 99%